2005
DOI: 10.1113/jphysiol.2004.080507
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ferret erythrocyte Na+–K+–2Cl cotransport by deoxygenation

Abstract: Deoxygenation of ferret erythrocytes stimulates Na+ -K + -2Cl − cotransport by 111% (S.D., 46) compared to controls in air. Half-maximal activation occurs at a P O 2 of 24 mmHg (S.D., 2) indicating that physiological changes in oxygen tension can influence cotransport function. Approximately 25-35% of this stimulation can be attributed to the rise of intracellular free magnesium concentration that occurs on deoxygenation (from 0.82 (S.D., 0.07) to 1.40 mM (S.D., 0.17)). Most of the stimulation is probably caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 53 publications
2
24
1
Order By: Relevance
“…Because NKCC-1 activity is thought to be increased by phosphorylation , it is likely that NKCC-1 phosphorylation during OGD increases [Cl Ϫ ] i . Consistent with this conclusion, Flatman (2005) reported that deoxygenation doubles NKCC-1 activity in ferret erythrocytes. This effect was blocked by a protein kinase inhibitor, indicating that it results from activation of protein kinases.…”
Section: Discussionsupporting
confidence: 75%
“…Because NKCC-1 activity is thought to be increased by phosphorylation , it is likely that NKCC-1 phosphorylation during OGD increases [Cl Ϫ ] i . Consistent with this conclusion, Flatman (2005) reported that deoxygenation doubles NKCC-1 activity in ferret erythrocytes. This effect was blocked by a protein kinase inhibitor, indicating that it results from activation of protein kinases.…”
Section: Discussionsupporting
confidence: 75%
“…A major candidate for the O 2 sensor was presumed to be Hb, because the O 2 dependence of the above properties generally follows the O 2 dissociation curve of Hb. 4,12,13 The downstream effector has been more uncertain, but band 3 has represented the prime candidate, because it constitutes the only established binding site of Hb on the membrane. Moreover, multiple observations document that the interaction between Hb and band 3 is O 2 -dependent, where association has been found to occur primarily, if not exclusively, with deoxygenated Hb.…”
mentioning
confidence: 99%
“…In rainbow trout, the effect of oxygen on transporter activity seems to be mediated through hydroxyl radicals, which stimulate KCC activity, whilst they inhibit the ␤NHE at high P O 2 (Bogdanova and Nikinmaa, 2001;Nikinmaa et al, 2003). The oxygen dependency of NKCC activity in RBCs of some tetrapods such as turkey and ferret and in crucian carp, however, is consistent with modulation by the Hb oxygenation state (Muzyamba et al, 1999;Flatman, 2005;Berenbrink et al, 2006). Shrinkage of B. marinus RBCs was attended by a pronounced amiloride-sensitive RVI response (Fig.·3C, Fig.·4C) that was much faster under deoxygenated conditions (Fig.·3B), reflecting the time course of activation and the magnitude of the Na influxes under the two levels of P O 2 (Fig.·1).…”
Section: Discussionmentioning
confidence: 79%
“…P O 2 dependency of shrinkage-induced Na influx and RVI Oxygenation-dependent RBC membrane transporters have now been described in nearly all vertebrate classes, ranging from lamprey to mammals (Motais et al, 1987;Nielsen et al, 1992;Gibson et al, 1998;Virkki et al, 1998;Muzyamba et al, 1999;Berenbrink et al, 2000;Berenbrink et al, 2006;Flatman, 2005) (reviewed by Gibson et al, 2000). This also applies to the transporters involved in volume regulation (Jensen, 1995;Nielsen, 1997;Gibson et al, 2000;Brauner et al, 2002;Drew et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation